2020
DOI: 10.1038/s41416-020-01063-5
|View full text |Cite
|
Sign up to set email alerts
|

Novel urinary protein biomarker panel for early diagnosis of gastric cancer

Abstract: Background With the goal of discovering non-invasive biomarkers for early diagnosis of GC, we conducted a case-control study utilising urine samples from individuals with predominantly early GC vs. healthy control (HC). Methods Among urine samples from 372 patients, age- and sex-matched 282 patients were randomly divided into three groups: 18 patients in a discovery cohort; 176 patients in a training cohort and 88 patients in a validation cohort. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 31 publications
0
33
0
Order By: Relevance
“…However, no urinary biomarkers have been clinically applied to malignant cases. We have been exploring for urinary biomarkers for a long time and found that urinary protein biomarkers are useful for gastric cancer 15 17 and colorectal cancer 18 . Moreover, we recently established a urinary miRNA biomarker panel using miR-6807-5p and miR-6856-5p; this panel can early detect gastric cancer 19 .…”
Section: Introductionmentioning
confidence: 99%
“…However, no urinary biomarkers have been clinically applied to malignant cases. We have been exploring for urinary biomarkers for a long time and found that urinary protein biomarkers are useful for gastric cancer 15 17 and colorectal cancer 18 . Moreover, we recently established a urinary miRNA biomarker panel using miR-6807-5p and miR-6856-5p; this panel can early detect gastric cancer 19 .…”
Section: Introductionmentioning
confidence: 99%
“…Microfluidic devices have been developed for urinary biomarker marker analysis which can be adapted to create a diagnostic platform for a variety of diseases [ 160 ]. These developments, as well as recent studies identifying candidate urinary protein biomarkers in gastric and prostate cancer, present urine as a promising medium for further proteomic analysis in blood cancers [ 161 , 162 ].…”
Section: Urinementioning
confidence: 99%
“…In contrast, there are far fewer studies on urinary biomarkers than on blood-based biomarkers for GI cancers. We and another group previously reported the usefulness of urinary protein and miRNA biomarkers in detecting GI cancers [ 4 , 7 , 8 , 9 , 10 ]. As urine is a completely non-invasive sample, urinary biomarker enables screening tests at home.…”
Section: Diagnostic Biomarkermentioning
confidence: 99%